Ethical attitudes of students and business professionals: A study of moral reasoning - Wood, John A. (Journal of business ethics, 1988)
A questionnaire on business ethics was administered to business professionals and to upper-class business ethics students. On eight of the seventeen situations involving ethical dilemmas in business, students were significantly more willing to engage in questionable behavior than were their professional counterparts. Apparently, many students were willing to do whatever was necessary to further their own interests, with little or no regard for fundamental moral principles. Many students and professionals functioned within Lawrence Kohlberg's stage four of moral reasoning, the “law and order” stage. Individualism and egoism remain strong patterns in the moral reasoning of many professionals, but they influence moral reasoning patterns among students to a much greater degree.